Information Technology for Consumer Interest Withdrawal - T Rohmawati; J Rahmayanti (Universitas Komputer Indonesia, 2021)
The purpose of this study is to determine the impact of social media content as a Consumer Interest Withdrawal Strategy. The method used in this study is a qualitative method by collecting data descriptively, namely by analyzing several online shops on the Instagram application. The results show that social media is used to buy products from the online shop. Online shop owners do not need to use a lot of money to arrange content on Instagram because it only requires creativity to make it more attractive, namely with themes, colors, and the preparation of content that is consistent. In conclusion, the development of technology provides a place for business people to start and continue business from marketing, promotion, to making consumers have a more efficient interest